2003
DOI: 10.1086/379116
|View full text |Cite
|
Sign up to set email alerts
|

Lyα Emission in Starbursts: Implications for Galaxies at High Redshift

Abstract: 0We present the results of a high resolution UV 2-D spectroscopic survey of star forming galaxies observed with HST-STIS. Our main aim was to map the Lyα profiles to learn about the gas kinematics and its relation with the escape of Lyα photons and to detect extended Lyα emission due to scattering in gaseous halos. We have combined our data with previously obtained UV spectroscopy on other three star-forming galaxies. We find that the P-Cygni profile is spatially extended, smooth and spans several kiloparsecs … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
213
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(237 citation statements)
references
References 49 publications
23
213
1
Order By: Relevance
“…Since Model 2 predicts higher intrinsic Hα/Hβ ratios than Model 1, the extinction derived in the diffuse emitting regions would be much lower than assuming case B, allowing for higher Lyα escape fractions in these areas. The ratio measured on Lyα ii , Lyα/Hα < 3.0, is compatible with the results found by Mas-Hesse et al (2003). They found that the diffuse Lyα emission exhibits a clear P Cyg profile all along slit D1, at any distance from the stellar knot SE.…”
Section: Photoionization By the Hot Plasmasupporting
confidence: 90%
See 2 more Smart Citations
“…Since Model 2 predicts higher intrinsic Hα/Hβ ratios than Model 1, the extinction derived in the diffuse emitting regions would be much lower than assuming case B, allowing for higher Lyα escape fractions in these areas. The ratio measured on Lyα ii , Lyα/Hα < 3.0, is compatible with the results found by Mas-Hesse et al (2003). They found that the diffuse Lyα emission exhibits a clear P Cyg profile all along slit D1, at any distance from the stellar knot SE.…”
Section: Photoionization By the Hot Plasmasupporting
confidence: 90%
“…We downloaded a pre-COSTAR PSF for an F/96 F220W observation performed five months earlier from the instrument website 1 and extracted the enclosed point source flux within the boundaries of the boxes we have considered. It was found that for the sizes (Mas-Hesse et al 2003), and D2 (G140L and G230L) (Chandar et al 2004), and the boxes used to extract the UV flux from each knot. The width of the slits is represented at real scale.…”
Section: Hst Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…One may expect a strong intrinsic Lyα emission for a low-metallicity galaxy but the observed Lyα output will also depend on other factors. Classical examples are IZw 18 and SBS 0335, the most metal-poor galaxies known, which show a strong absorption in Lyα (Kunth et al 1998;Mas-Hesse et al 2003;Atek et al 2009b). In fact, the metallicity distributions of the LAEs and UV-continuum galaxies measured in Cowie et al (2011) overlap significantly.…”
Section: Effects Of Metallicitymentioning
confidence: 99%
“…Such double peaked profiles of optical emission lines have been observed for nearby starburst galaxies which exhibit these large scale outflows typically termed superwinds (Heckman et al 1990). Additionally, a double peaked Lyα emission line profile was found from the starburst galaxy T1214-277 by Mas-Hesse et al (2003), who concluded that the feature is caused by emission in an outflow. Double-peaked Lyα profiles have been observed also at redshift z ∼ 3, in spectra of star forming galaxies (Fosbury et al 2003;Christensen et al 2004;Venemans et al 2005;Tapken et al 2007).…”
Section: Individual Notesmentioning
confidence: 99%